Synthesis of Chiral Spiro[4.5]decadienones via Chirality-Transferring Oxidative Intramolecular Cyclization of Allenylsilane-Tethered Phenols - Kishimoto, Ryoma; Iwakiri, Yuka; Sakaguchi, Kazuhiko; Nishimura, Takahiro (Synthesis, 2023)
Reactions of phenols having a methylene-tethered chiral allenylsilane at the para position with a hypervalent iodine reagent result in chirality-transferring oxidative intramolecular cyclization accompanied by dearomatization of the phenol to stereoselectively give spiro[4.5]decadienones possessing a silylethynyl group.
Keywords: allenylsilane; hypervalent iodine; chirality transfer; oxidative intramolecular cyclization; spirodienone; phenol